IL-12p40 is not required for islet allograft rejection - Bi En-guang; Shi Wei; Zou Jia; Hao Zhen-hua; Li Zhen-hu; Cai Duan; Zhang Hua-qun; Sun Bing (Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether IL-12p40 plays a crucial role in regulating islet allograft rejection in a streptozotocin (STZ)-induced diabetes mouse model. Methods: C57BL/6 and IL-12p40 gene knockout mice were selected as recipient mice, to which the diabetes was induced with a treatment of STZ (150–200 mg/kg) by a single ip injection. BALB/c mice were selected as donor mice and islet cells were isolated from the mice. The 500 islets were transplanted into recipient mice beneath the capsule of the left kidney. Following the islet transplantation the glucose from the mice sera was monitored and the rejection rate of islets was analyzed. Results: STZ could induce diabetes in the recipient mice within 1 week. After transplantation of allograft islets, the increased glucose in wild-type (WT) mice returned to normal level and was maintained for 10 d. Unexpectedly, the rejection rate of islet allograft between IL-12p40-deficient mice and WT mice was similar. Conclusion: The results suggested that, although islet allograft rejection is believed to be Th1-cell predominant, the Th1 response inducer, IL-12 and IL-23 are not essential to induce islet allograft rejection.